Research on the impact and mechanism of local governments' land conveyance behavior on urban-rural integrated development-Empirical evidence from 281 prefecture-level cities in China. - Long Zeng; Bin Peng; Jin Xie (PLoS ONE)
The land sale practices of local governments significantly impact urban-rural integration development. This paper utilizes panel data from 281 prefecture-level and above cities in China, using local government land sale practices as a logical starting point. It examines the effects and mechanisms of these practices on urban-rural integration development from two dimensions: land price competition and land finance dependence, employing a bidirectional fixed effects model among other empirical tests. The findings indicate that land price competition has a significant positive effect on urban-rural integration development, showing an inverted U-shaped relationship. In contrast, land finance dependence hinders urban-rural integration development. The impact of local government land sale practices on urban-rural integration development also varies by region, administrative level, and different aspects of urban-rural integration. Furthermore, local government land sale practices mainly influence urban-rural integration development through labor transfer effects, public service provision effects, and industrial structure upgrading effects. Labor transfer and industrial structure upgrading play significant positive moderating roles in promoting urban-rural integration development through land price competition. Public service provision and industrial structure upgrading play significant positive moderating roles in mitigating the inhibitory effects of land finance dependence on urban-rural integration development.